Virtual simulation with AneuShape™ software for microcatheter shaping in intracranial aneurysm coiling: a validation study - Wu, Zeng-Bao; Zeng, Ying; Zhang, Hua-Qiu; Shu, Kai; Li, Gao-Hui; Xiang, Jian-Ping; Lei, Ting; Zhu, Ming-Xin (Frontiers in Neurology, 2023)
Background: An accurate and stable microcatheter shaping plays a vital role in the successful embolization of intracranial aneurysms. Our study aimed to investigate the application and the role of AneuShapeTM software in microcatheter shaping for intracranial aneurysm embolization. Methods: From January 2021 to June 2022, 105 patients with single unruptured intracranial aneurysms were retrospectively analyzed with or without AneuShapeTM software to assist in microcatheter shaping. The rate of microcatheter accessibility, accurate positioning, and stability for shaping were analyzed. During the operation, fluoroscopy duration, radiation dose, immediate postoperative angiography, and procedure-related complications were evaluated. Results: In comparison with the manual group, the procedure performed with the AneuShapeTM software gained a lower rate of reshaping microcatheter (21.82% vs. 44.00%, p = 0.015,) and a higher rate of accessibility (81.82% vs. 58.00%, p = 0.008,) and achieved better position (85.45% vs. 64.00%, p = 0.011) and higher stability (83.64% vs. 62.00%, p = 0.012). For both small (<7mm) and large (≥7mm) aneurysms, the software group used more coils than the manual group (3.50 ±0.19 vs. 2.78 ±0.11, p = 0.008 and 8.22 ±0.36 vs. 6.00 ±1.00, p = 0.081, respectively). In addition, the software group gained better complete or approximately complete aneurysm obliteration (87.27% vs. 66.00%, p = 0.010), as well as a lower procedure-related complication rate (3.60% vs. 12.00%, p = 0.107). Without this software, the operation had a longer intervention duration (34.31 ±6.51 min vs. 23.87 ±6.98 min, p < 0.001) and a higher radiation dose (750.50 ±177.81 mGy vs. 563.53 ±195.46 mGy, p < 0.001). Conclusions: Software-based microcatheter shaping techniques can assist the precise shaping of microcatheters, reduce operating time and radiation dose, improve embolization density, and facilitate more stable and efficient intracranial aneurysm embolization.